An overview of mice models : a key for understanding subtypes of mania (2016)
ABSTRACT: Animal models have been broadly used inthe study of pathophysiology and molecular and neurochemical pathways in neuropsychiatric diseases. Different approaches have used both consanguineous and non-consanguineous mice models to model behavioral patterns associated with the maniac spectrum. However, the disadvantages of validating clinical and experimental protocols have hindered the replication of these studies. In this article, the advantages and disadvantages of using consanguineous lines and non-consanguineous stocks in mice animal models for the study of mania and its subtypes are discussed. Additionally, new experimental alternatives to advance the pathogenesis and pharmacogenetics of mania using animal models are proposed and analyzed.